Regular protocol liver biopsy is useful to adjust immunosuppressant dose after adult liver transplantation. Issue 3 (22nd December 2022) - Narita, Shohei; Miuma, Satoshi; Okudaira, Sadayuki; Koga, Yoshito; Fukushima, Masanori; Sasaki, Ryu; Haraguchi, Masafumi; Soyama, Akihiko; Hidaka, Masaaki; Miyaaki, Hisamitsu; Futakuchi, Mitsuru; Nagai, Kazuhiro; et al.
Abstract: Introduction: Adjusting immunosuppression to minimal levels post‐adult liver transplantation (LT) is critical; however, graft rejection has been reported in LT recipients with normal liver function evaluated by liver biopsy (LBx). Continual protocol liver biopsy (PLB) is performed regularly in LT recipients with normal liver function in some centers; however, its usefulness remains inadequately evaluated. This study aimed to assess retrospectively the usefulness of late PLB after adult LT. Methods: LBx evaluations of LT recipients with normal liver function and hepatitis B and C virus seronegativity were defined as PLB. The cases requiring immunosuppressive therapy for rejection findings based on Banff criteria were extracted from the PLBs, and pathological data collected before and after immunosuppressive dosage adjustment (based on modified histological activity index [HAI] score) were compared. Results: Among 548 LBx cases, 213 LBx in 110 recipients fulfilled the inclusion criteria for PLB. Immunosuppressive therapy after PLB was intensified in 14 LBx (6.6%) recipients (12.7%); of these, nine had late‐onset acute rejection, three had isolated perivenular inflammation, one had plasma cell‐rich rejection, and one had early chronic rejection. Follow‐up LBx after immunosuppressive dose adjustment showed improvement in the modified HAI score grading in 10 of 14 cases (71.4%). No clinical background and blood examination data, including those from the post‐LT period, immunosuppressant trough level, or examination for de novo DSA, predicted rejection in PLB. Complications of PLB were found in only three cases. Conclusion: PLB is useful in the management of seemingly stable LT recipients, to discover subclinical rejection and allow for appropriate immunosuppressant dose adjustment.